Role of aloin in the modulation of certain immune parameters in skin mucus of an Indian major carp, Labeo rohita. Issue 73 (February 2018) - Srivastava, Ayan; Nigam, Ashwini Kumar; Mittal, Swati; Mittal, Ajay Kumar
Abstract: Enhancement of immune system seems to be the most promising method of preventing fish diseases. Several herbal products have immunostimulant properties, and are environmental friendly, economical and can act against a broad spectrum of pathogens. Present study was designed with an aim to evaluate the role of aloin, extracted from a herb Aloe barbadensis, in the modulation of certain immune parameters in an Indian major carp, Labeo rohita . Fishes were divided into control, vehicle control and aloin treated groups. Experiments were conducted for 7 days and fishes from the three groups were analyzed at 2d, 4d, 6d and 8d. The results demonstrated that at different intervals, L. rohita administered with aloin showed a significant increase in the activity of enzymes – lysozyme, protease, carboxylesterase, alkaline phosphatase, acid phosphatase, catalase and peroxidase, and non-enzymatic factors hemagglutinin and alternate complement compared with that of the controls. Thus, it can be concluded that administration of aloin is beneficial in enhancing the immune response and hence it can be used as potent immunostimulant in aquaculture. Highlights: Role of aloin in modulation of certain immune parameters in L. rohita is reported. Aloin treated fish shows significant increase in the activity of immune parameters. The study shows that aloin is beneficial in enhancing the immune response in fish.